Upaya menurunkan morbiditas dan mortalitas ibu hamil melalui penyuluhan dan skrining risiko kehamilan di Kelurahan Tuan Kentang Palembang - Rista Silvana; Ratih Pratiwi; Ary Rinaldzi (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2020)
Efforts to reduce maternal morbidity and mortality through counseling and pregnancy risk screening in at Kelurahan Tuan Kentang Palembang. The maternal mortality rate in South Sumatra is still high. Maternal morbidity and mortality can be avoided by having regular antenatal care (ANC) visits. Although the coverage of ANC in Indonesia is increasing, the number in South Sumatra is still below the national average. Education is needed to increase the knowledge of mothers so that they routinely have pregnancy visits. The aim of the community service in Tuan Kentang Village are to improve knowledge of the importance of ANC and provide pregnancy risk screening to reduce maternal morbidity and mortality. A total of 20 pregnant women participated in this activity. Only nine people (45%) performed ANC in sufficient numbers. Low level of education, lack of knowledge about ANC, and distance to health services are factors that prevent mothers from doing ANC. As many as 17 people (85%) had high risk pregnancies due to age, parity, previous pregnancy history, fetal abnormalities, maternal diseases related to pregnancy or infection, and gynecological disorders. Most of the participants did less ANC visits, and were in the high pregnancy risk category.